FACTORS AFFECTING SERVICE QUALITY IN THE IMPLEMENTATION OF RESEARCH AND COMMUNITY SERVICE PROGRAMMES AT PRIVATE UNIVERSITIES WITHIN THE REGIONAL HIGHER EDUCATION SERVICE INSTITUTION I - Siregar, Robert Tua; Damanik, Ronald; Sofiyan, Sofiyan; Sitanggang, Tina Novianti; Toni, Nagian; Purba, Melfrianti Romauli (JURNAL MANAJEMEN MAKER STIE SULTAN AGUNG, 2026)
This study aims to identify and analyze the factors that affect service quality in the implementation of research and community service programmes at private universities under the coordination of the Higher Education Service Institution (LLDIKTI) Region I. As part of its mandate, LLDIKTI is responsible for supervising, assisting, and improving the quality of higher education services, particularly in research and community service funded through national grant schemes. Using a quantitative approach, data were collected from 102 respondents consisting of heads of Research and Community Service Institutions (LPPM) at private universities who received BOPTN grant funding. Data analysis was performed using SPSS version 25, including validity testing, reliability testing, classical assumption tests, multiple linear regression, t-test, F-test, and coefficient of determination. The results show that the variables tangibles, responsiveness, and assurance have a positive and significant effect on service quality, indicating that physical facilities, the promptness of service, and confidence in institutional capability strongly shape user perceptions. In contrast, reliability and empathy show no significant effect on service quality. Simultaneously, all variables significantly influence service quality, demonstrating that service quality is multifaceted and reliant on interconnected dimensions. These findings highlight the need for LLDIKTI Region I to strengthen its physical infrastructure, improve responsiveness, and ensure the professionalism of its services to enhance satisfaction among higher education institutions.